2001
DOI: 10.1524/zpch.2001.215.6.777
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Shift in the Frequencies of the CH Stretches of Chloro- and Fluoroform Induced by C–H...π Hydrogen Bonding with Benzene Derivatives: the Influence of Electron Donating and Withdrawing Substituents

Abstract: Mixed clusters of benzene derivatives and trihalogenmethanes have been prepared in a supersonic beam and studied with infrared vibrational predissociation spectroscopy detected by resonant two photon ionization (IR/R2PI). We report the spectra of chloroform and fluoroform attached to the chromophores fluorobenzene, benzene, toluene, p-xylene and their deuterated analogues. Instead of the typical H-bonding induced red-shift of the CH stretching frequency a blue-shift is observed. From a comparison with ab initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In 1999, an increase of C–H stretching frequency was reported in the complex between chloroform and fluorobenzene by using double-resonance IR ion-depletion spectroscopy . In addition, a surprising shortening of the C–H bond was found in C–H...O/N/halogen/π H-bonds. The BSHB is often reported for H-bond complexes formed between various proton acceptors and the proton donor C sp3 –H (C sp3 refers to the tetrahedral hybridized carbon in the molecule). ,, For example, complexation between methane, fluoroform, chloroform, bromoform, and iodoform on the one hand and water, benzene, fluorobenzene, acetylene, and ethylene ,,, on the other hand leads to a C–H bond contraction.…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, an increase of C–H stretching frequency was reported in the complex between chloroform and fluorobenzene by using double-resonance IR ion-depletion spectroscopy . In addition, a surprising shortening of the C–H bond was found in C–H...O/N/halogen/π H-bonds. The BSHB is often reported for H-bond complexes formed between various proton acceptors and the proton donor C sp3 –H (C sp3 refers to the tetrahedral hybridized carbon in the molecule). ,, For example, complexation between methane, fluoroform, chloroform, bromoform, and iodoform on the one hand and water, benzene, fluorobenzene, acetylene, and ethylene ,,, on the other hand leads to a C–H bond contraction.…”
Section: Introductionmentioning
confidence: 99%
“…In a few cases, however, experiments find that the X−H stretching vibration is shifted toward higher frequency (blue-shift) in an X−H···Y hydrogen-bonded system, where X is CF 3 and CCl 3 , and Y is triformylmethane, benzene, ethylene oxide, and dimethyl ether. A number of theoretical studies have also demonstrated that blue-shifted hydrogen bonds can be obtained at various levels of calculation. Clearly, this challenges the generally held explanations of hydrogen bonding and the standard experimental methods of detecting hydrogen bonds, because the qualitative theoretical models mentioned above only allow for red-shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the relatively higher acidity of acetylenic CH (p K a = 25) than those of alkane (p K a = 49 for methane) and alkene (p K a = 44 for ethylene), the interaction between acetylenic CH and π-electrons is considered to be relatively stronger , and both of them are often called activated CH/π interaction . Infrared (IR) spectroscopic studies of bulk solutions have demonstrated that low-frequency shifts of the CH stretching vibration of various substituted acetylenes occur upon association with aromatic molecules .…”
Section: Introductionmentioning
confidence: 99%